The relationship between management team (TMT) metacognition, entrepreneurial orientations and small and medium enterprises (SMEs) firm performance. (2018) - Rhodes, Jo; Cheng, Vincent; Sadeghinejad, Zahra; Lok, Peter
This study examines the impact of top management team (TMT) metacognition on entrepreneurial orientation and firm performance. The result revealed that the mediation effect of 'managing risk' in TMT entrepreneurial orientation has a negative impact on SMEs performance. Hence, TMT in SMEs should focus their strategic decisions on innovativeness and proactiveness rather than high risk projects to remain competitive. Furthermore, the findings further supported that effective behavioural integration of TMT could significantly influence the outcome of TMT metacognition and entrepreneurial orientation. 1500 SMEs were surveyed in this study.